Red luminescence properties of Te4+-doped CaYAlO4 phosphors. Issue 12 (15th June 2021) - Song, Hanzhao; Wu, Wanying; Xing, Zhifeng; Zhou, Xunsheng; Yao, Aihua; Hu, Shanshan; Hong, Ying; Wang, Baolong; Lu, Shuang; Wang, Yinzhen
Abstract: Novel Te 4+ -doped CaYAlO4 phosphors were obtained by a solid-state reaction. Te 4+ -doped CaYAlO4 samples had a tetragonal crystal structure and emit deep-red light at 715 nm excited by 325 nm, which was ascribed to Te 4+ luminescence center. The luminescent intensity of CaYAlO4 : Te 4+ samples increased with the sintering temperature increasing, reaching a maximum at 1500 °C, then began to drop. The optimal Te 4+ doping concentration was 2 mol%. Lifetime of CaYAlO4 : 2%Te 4+ phosphors was 1.54 ms. The luminescent intensity of CaYAlO4 : 2%Te 4+ phosphors decreased with the increase of test temperature and reached to 35.0% of the initial value at 425 K. The CaYAlO4 : Te 4+ phosphors have potential applications in bio-imaging, temperature sensor, solid-state lighting and solar cells etc. Graphical abstract: Image 1 Highlights: Te 4+ -doped CaYAlO4 phosphors were synthesized by a solid-state method. Te 4+ -doped CaYAlO4 phosphors can emit efficient deep-red light at 715 nm excited by 325 nm. Te 4+ -doped CaYAlO4 phosphors had long lifetime of 1.54 ms.